2020
DOI: 10.1073/pnas.2001914117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a chemical fingerprint linking the undeclared 2017 release of 106 Ru to advanced nuclear fuel reprocessing

Abstract: The undeclared release and subsequent detection of ruthenium-106 (106Ru) across Europe from late September to early October of 2017 prompted an international effort to ascertain the circumstances of the event. While dispersion modeling, corroborated by ground deposition measurements, has narrowed possible locations of origin, there has been a lack of direct empirical evidence to address the nature of the release. This is due to the absence of radiological and chemical signatures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…For example, in the IAEA database, the majority of the reported incidences involve trafficking of a small quantity of fissile or other radioactive materials, raising concerns about the spreading of radioactivity in the environment. Nuclear forensics, a multidisciplinary branch of analytical science, can play a key role in strengthening safeguard capabilities and ensuring global nuclear security by deterring diversion incidences, even in very small quantities, and providing sufficient evidence on the origin and intended purposes in case of a seizure, that may be useful for legal proceedings. With the advent of advanced analytical methodologies and improved computational capabilities, the branch of nuclear forensics has witnessed rapid development in the recent past and has been able to solve challenging forensic problems using experiments and artificial intelligence/machine learning techniques. …”
Section: Introductionmentioning
confidence: 99%
“…For example, in the IAEA database, the majority of the reported incidences involve trafficking of a small quantity of fissile or other radioactive materials, raising concerns about the spreading of radioactivity in the environment. Nuclear forensics, a multidisciplinary branch of analytical science, can play a key role in strengthening safeguard capabilities and ensuring global nuclear security by deterring diversion incidences, even in very small quantities, and providing sufficient evidence on the origin and intended purposes in case of a seizure, that may be useful for legal proceedings. With the advent of advanced analytical methodologies and improved computational capabilities, the branch of nuclear forensics has witnessed rapid development in the recent past and has been able to solve challenging forensic problems using experiments and artificial intelligence/machine learning techniques. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that the volatile and highly reactive RuO 4 was the origin of the release of the radioactive pollution. [2][3][4] While specific porous adsorbent media, such as activated charcoals or silver exchanged zeolites, have been used for decades for the capture of radiotoxic gaseous iodine ( 129/131 I), 5 the development of a specific process remains much less explored for the immobilization or the separation of gaseous RuO 4 . Typically, in spent fuel reprocessing, gaseous RuO 4 precipitates on cold surfaces as a black nonvolatile RuO 2 deposit, which makes its separation from other radioactive wastes difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that the volatile and highly reactive RuO 4 was the origin of the release of the radioactive pollution. 2–4…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, and despite strong circumstantial evidence, the case was considered unproven when Richard Wakeford provided an update in the March 2020 issue of this journal [7]. The situation may be about to change following the publication of two recent papers dealing with, respectively, the chemical speciation of deposited 106 Ru [8] and isotopic fingerprinting involving stable ruthenium isotopes [9]. These high sensitivity analyses of filter papers from air sampling stations in Austria, Germany and Sweden confirm the unusual radioactive inventory, which contains only the beta-emitting fission product 106 Ru together with ultra-trace quantities of 103 Ru [8,9].…”
mentioning
confidence: 99%